2008
DOI: 10.1093/nar/gkn443
|View full text |Cite
|
Sign up to set email alerts
|

Intronically encoded siRNAs improve dynamic range of mammalian gene regulation systems and toggle switch

Abstract: Applications of conditional gene expression, whether for therapeutic or basic research purposes, are increasingly requiring mammalian gene control systems that exhibit far tighter control properties. While numerous approaches have been used to improve the widely used Tet-regulatory system, many applications, particularly with respect to the engineering of synthetic gene networks, will require a broader range of tightly performing gene control systems. Here, a generically applicable approach is described that u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 64 publications
0
49
0
Order By: Relevance
“…(C) Schematic diagram for two representative logic gates, the XOR and AND gates reviewed by Singh et al [75]. demonstrated in multiple organisms [18,24,76], and examples of similar topologies are rife in nature [68]. A system can also express multistable behavior through autoactivation [74].…”
Section: Multistability Of Grnsmentioning
confidence: 99%
“…(C) Schematic diagram for two representative logic gates, the XOR and AND gates reviewed by Singh et al [75]. demonstrated in multiple organisms [18,24,76], and examples of similar topologies are rife in nature [68]. A system can also express multistable behavior through autoactivation [74].…”
Section: Multistability Of Grnsmentioning
confidence: 99%
“…These circuits are particularly useful to program mammalian processes with binary characteristics such as differentiation or apoptosis. This transcriptional switch was later improved and used in living mice [40], demonstrating its potential for precise long-term protein delivery in the absence of a sustained input, a critical feature when long term drug administration is potentially toxic or expensive.…”
Section: The Synthetic Tool Kitmentioning
confidence: 99%
“…Bioengineers have used RNAi to tighten control and tweak the expression dynamics of synthetic systems. Greber et al (2008) demonstrated that intronic short interfering RNAs (siRNAs) can reduce basal gene expression of inducible transcription systems (Greber et al 2008). Deans et al (2007) designed an inducible switch in mammalian cells that produces shRNAs to prevent leaky expression of transgenes (Fig.…”
Section: Translational Regulationmentioning
confidence: 99%